Drinking jelly from khlu (Pluchea indica less.) leaves tea with antioxidative and anti-inflammatory activities - Kungsanant, Suratsawadee; Kangsanant, Sureeporn (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to develop a functional ready-to-drink jelly from Pluchea indica (L.) Less. leaves (“Khlu” in Thai), focusing on antioxidant and anti-inflammatory properties influenced by extraction method and sweetener concentration. Green and black tea preparation methods were compared, and the resulting infusions were used to formulate jelly products. Monk fruit sweetener was incorporated at four concentrations (0.5%, 0.75%, 1.00%, and 1.25% w/v) to evaluate its effect on taste and appearance. Antioxidant activity was assessed using the DPPH assay, while anti-inflammatory properties were measured via nitric oxide (NO) inhibition in macrophage cells. The black tea preparation showed significantly higher DPPH radical scavenging activity (423.36 mmol FAE/100 g) than green tea, indicating a stronger antioxidant capacity. Interestingly, although its total phenolic content (0.864 ± 0.006 mg GAE/g) was slightly lower than that of green tea, it exhibited greater NO inhibition at 10 mg/ml, suggesting the presence of other potent bioactive compounds generated during oxidation. Cytotoxicity testing revealed no toxicity at concentrations ≤10 mg/ml. Sensory evaluation using a 9-point hedonic scale identified 1.00% monk fruit as the most preferred level, balancing sweetness, color, and overall acceptability. Higher concentrations (≥1.25%) led to darker jelly and lower scores for visual appeal. Nutritional analysis of the optimized product (per 100 g) showed 98.54 g of moisture, 1.13 g of carbohydrate, 0.15 g of protein, 0.18 g of ash, no detectable fat, and a low caloric value of 5.10 kcal. These findings suggest that jelly prepared with black tea extract and 1.00% monk fruit sweetener delivers desirable functional properties, safety, and consumer appeal. The product shows strong potential as a novel low-calorie, antioxidant-rich beverage for health-conscious consumers and could be further explored for commercial applications.